ANALISA KINERJA PENYALURAN KREDIT TERHADAP RISIKO KREDIT PADA BANK PERKREDITAN RAKYAT TAHUN 2016 - 2019 - Wangsit Supeno; Ketut Martana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Abstract Based on Indonesian banking statistics in 2019, the rural bank (BPR) has a positive performance in the growth of credit distribution. This credit growth shows that rural bank (BPR) function in carrying out credit-giving activities is still gaining trust from the community, so it still has its existence and opportunities to increase Credit distribution amid increasingly sharp competition. The distribution of working capital loans in 2019, has a positive impact on the growth of the most dominant economic sector, namely trade, agriculture and services in every province where the rural bank (BPR) operates. While investment credit distribution also helps many people in the sector of trade and community services. The consumptive credit distribution helps the community who needs funds for other urgent consumption sectors. In connection with the growth of the credit of the creditor of the rural bank (BPR) in 2019, the management of the rural bank (BPR) should pay attention to the level of credit risk arising by measuring the ratio of Non-Performing Loan (NPL), so that the rural bank (BPR) can take effective and efficient anticipation measures so that the credit delivered can improve the healthy and profitable assets.